2010
DOI: 10.1111/j.1600-0897.2009.00781.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Role of Inflammatory Cytokines and eNOS Gene Polymorphism in Pathophysiology of Pre‐Eclampsia

Abstract: An IL-6-mediated endothelium dependent NO-cyclic guanine monophosphate-mediated relaxation pathway may be inhibited in systemic vessels in pre-eclampsia. As observed in this study Glu298Asp eNOS gene polymorphism did not showed significant association with pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 35 publications
1
18
2
Order By: Relevance
“…Several polymorphisms in NOS3 gene were identified, of which three common functional polymorphisms were studied. These comprise the promoter -786T>C (rs2070744) single-nucleotide polymorphism (SNP) (Aggarwal et al, 2010;Lizbeth et al, 2011;Sandrim et al, 2010), the 4b/4a (rs61722009) variable number of 27 bp-repeat tandem repeats in intron 4 ( Rahimi et al, 2013;Sandrim et al, 2010;Singh et al, 2010), and the functional Glu298Asp (rs1799983) exon 7 variant, G to T substitution at nucleotide position 894 resulting in the replacement of glutamic acid with aspartic acid at codon 298 the Glu298Asp (Rahimi et al, 2013;Turan et al, 2010;Yu et al, 2006). However, conflicting and controversial results were reported among different studies.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…Several polymorphisms in NOS3 gene were identified, of which three common functional polymorphisms were studied. These comprise the promoter -786T>C (rs2070744) single-nucleotide polymorphism (SNP) (Aggarwal et al, 2010;Lizbeth et al, 2011;Sandrim et al, 2010), the 4b/4a (rs61722009) variable number of 27 bp-repeat tandem repeats in intron 4 ( Rahimi et al, 2013;Sandrim et al, 2010;Singh et al, 2010), and the functional Glu298Asp (rs1799983) exon 7 variant, G to T substitution at nucleotide position 894 resulting in the replacement of glutamic acid with aspartic acid at codon 298 the Glu298Asp (Rahimi et al, 2013;Turan et al, 2010;Yu et al, 2006). However, conflicting and controversial results were reported among different studies.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Guo et al, 1999;Singh et al, 2010;Turan et al, 2010). Insofar as plasma NO levels are dependent on environmental and genetic factors, it was shown that-786T>C, Glu289Asp and 4b/4a NOS3 variants can alter the secretion and function ofNO (Deng et al, 2010; Zdoukopoulos et al, 2011).…”
mentioning
confidence: 96%
“…However, subsequent studies from various populations did not support a role for this polymorphism in the pathogenesis of preeclampsia. The studies of Hakli et al [17] from eastern Finland, Yoshimura et al [18] from Bangladesh, Landau et al [19] among Hispanic and white women, Singh et al [20] from India and Yu et al [21] from England did not detect an association between this polymorphism and the risk of preeclampsia. Also, in the study by Sandrim et al [22] no association was detected between two eNOS polymorphisms (G894T and T786C) and the risk of preeclampsia.…”
Section: Discussionmentioning
confidence: 94%
“…The role of endothelial nitric oxide synthase (eNOS) polymorphism in the pathogenesis of preeclampsia is debated [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Several polymorphisms in NOS3 were identified in this study, among which, three common functional polymorphisms, the promoter -786T>C (rs2070744) SNP (Aggarwal et al, 2010), the 4b/4a (rs61722009) variable number of tandem repeats (27-bp repeat) in intron 4 (Singh et al, 2010;Rahimi et al, 2013), and the functional Glu298Asp (rs1799983) exon 7 variant (a G-to-T substitution at position 894 resulting in the replacement of glutamic acid with aspartic acid at codon 298) (Yu et al, 2006;Turan et al, 2010), were investigated. Recent clinical trials have proven the beneficiary effects of inhaled NO on respiratory syndromes (Schreiber et al, 2003;Ballard et al, 2006).…”
Section: Discussionmentioning
confidence: 99%